Fabrication of portable chemical sensor for highly selective thiocyanate detection based on Co(II) porphyrin complex / Siti Nuraqidah Zainal - Siti Nuraqidah , Zainal (2018)
Fabrication of portable chemical sensor for highly selective thiocyanate (SCN) detection based on Co(II) porphyrin complex with self-plasticizing membrane involves 5,10,15,20-tetrakis-(4-methoxyphenyl)-21H,23H-porphyrin Co(II) or CoTMeOPP as the ionophore, n-butyl acrylate (n-BA) and 2-Hydroxyethyl methacrylate (HEMA) self-plasticizing polymers as the membranes, tetradodecylammonium chloride (TDDA) as additive and glassy carbon electrode (GCE) as the transducer. This ionophore was proven to diverge from the classic Hofmeister theory, have highly selectivity towards thiocyanate anion and stable to work with the self-plasticizing membrane. The new optimized potentiometric self-plasticizing of CoTMeOPP highly selective complexation with SCN- has been studied by using potentiometer and the stoichiometric of the complexation reactions of Co2+/3+ and SCN- is 2:1 [Co2+/3+: SCN-]. The optimum membrane composition was obtained by using silver/silver chloride (Ag/AgCl) as the first layer, 95.14 wt.% monomer (HEMA) and 4.86 wt.% photo initiator (DMPP) as the second layer and 98.86 wt.% monomer (n-BA), 0.08 wt.% photo initiator (HDDA), 0.34 wt.% ionophore (CoTMeOPP), 0.16 wt.% lipophilic salt (TDDA) and 0.56% photo initiator (DMPP). The fabricated SCN-ISE was tested with standard solution of SCN- and exhibits a good Nernstian behavior with the slope of -60.76 mV/decade and detection limit of 9.55×10-8 mol/L over a wide concentration range of 1.0×10−7 mol/L to 1.0×10−1 mol/L. The fabricated sensor displayed wide working pH range from 2 to 11, short response time (68 seconds), low resistance and excellent selectivity relative to a wide variety of other anions, good repeatability and reproducibility. The fabricated electrode can be used over a period of seven days provided kept in refrigerator without itself showing any significant drift in working concentration range, slope and response time. The fabricated SCN-ISE sensor was successfully applied for the determination of thiocyanate in real samples with satisfactory recovery ranges i.e more than full percentage.